Irrigating Lettuce with Wastewater Effluent: Does Disinfection with Chlorine Dioxide Inactivate Viruses?. Issue 5 (1st September 2018) - López‐Gálvez, F.; Randazzo, W.; Vásquez, A.; Sánchez, G.; Decol, L. Tombini; Aznar, R.; Gil, M.I.; Allende, Ana
Abstract : Reclaimed water obtained from urban wastewater is currently being used as irrigation water in water‐scarce regions in Spain. However, wastewater can contain enteric viruses that water reclamation treatment cannot remove or inactivate completely. In the present study, greenhouse‐grown baby lettuce ( Lactuca sativa L.) was irrigated with secondary treatment effluent from a wastewater treatment plant untreated and treated using chlorine dioxide (ClO2 ). The effect of ClO2 treatment on the physicochemical characteristics and the presence of enteric viruses in irrigation water and lettuce was assessed. The presence of human noroviruses genogroups I and II (NoV GI and NoV GII), and human astroviruses (HAstV), was analyzed by real‐time polymerase chain reaction (RT‐qPCR). Additionally, to check for the loss of infectivity induced by the disinfection treatment, positive samples were re‐analyzed after pretreatment with the intercalating dye PMAxx before RNA extraction and RT‐qPCR. There were no significant differences in the proportion of positive samples and the concentration of enteric viruses between treated and untreated reclaimed water without PMAxx pretreatment ( p > 0.05). A significantly lower concentration of NoV GI was detected in ClO2 –treated water when samples were pretreated with PMAxx ( p < 0.05), indicating that inactivation was due to the disinfection treatment. Laboratory‐scale validation tests indicated the suitability of PMAxx‐RT‐qPCR for discrimination between potentially infectious and ClO2 –damaged viruses. Although the applied ClO2 treatment was not able to significantly reduce the enteric virus load of the secondary effluent from the wastewater treatment plant, none of the lettuce samples analyzed ( n = 36) was positive for the presence of NoV or HAstV. Core Ideas: Reclaimed water used for irrigation can contain enteric viruses. Current detection methods do not distinguish infectious from noninfectious viruses. PMAxx treatment can help to get information on the infectivity of viral particles. Treatment of reclaimed water with ClO2 did not improve irrigation water safety.